2015
DOI: 10.5455/msm.2015.27.328-332
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Measuring Tuberculosis Therapy Compliance: Greece as a Host Country for Vulnerable Populations Before and During the Financial Crisis

Abstract: Background:For the realization of “2015 UN Millennium Development Goals”, a question arises pertaining to the course of tuberculosis in Greece and its relationship to patient adherence to treatment, given the fact that the country is undergoing a financial crisis and is a gateway for economic migrants.Methods:The study concerned 1179 patients of the anti-TBdepartment, “Sotiria” General Chest Diseases Hospital, Athens, Greece collaborating with the National Reference Centre of Mycobacteria, covering a year befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The figures of noncompliance in nonpsychiatric patients in some Indian studies are HIV-30%,[ 22 ] tuberculosis-6 to 50%[ 23 24 25 ] multidrug-resistant tuberculosis-19%,[ 26 ] hypertension-28.9%,[ 27 ] diabetes mellitus-42.3%,[ 28 ] head and neck cancer-23.5%,[ 29 ] cervical cancer-61.1%,[ 30 ] curative cancer treatment-33.33%,[ 31 ] lung cancer-36%. [ 32 ] Even in studies conducted abroad noncompliance has been reported in various medical conditions; tuberculosis global noncompliance rate-61.7%,[ 33 ] HIV optimal treatment-68%,[ 34 ] hypertension-30.5%,[ 35 ] diabetes mellitus (new detection)-20.6%. [ 36 ] It has been reported that adequate adherence is found only in the 1 st year of treatment in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The figures of noncompliance in nonpsychiatric patients in some Indian studies are HIV-30%,[ 22 ] tuberculosis-6 to 50%[ 23 24 25 ] multidrug-resistant tuberculosis-19%,[ 26 ] hypertension-28.9%,[ 27 ] diabetes mellitus-42.3%,[ 28 ] head and neck cancer-23.5%,[ 29 ] cervical cancer-61.1%,[ 30 ] curative cancer treatment-33.33%,[ 31 ] lung cancer-36%. [ 32 ] Even in studies conducted abroad noncompliance has been reported in various medical conditions; tuberculosis global noncompliance rate-61.7%,[ 33 ] HIV optimal treatment-68%,[ 34 ] hypertension-30.5%,[ 35 ] diabetes mellitus (new detection)-20.6%. [ 36 ] It has been reported that adequate adherence is found only in the 1 st year of treatment in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…For Greece in particular, the protracted and severe financial crisis was combined with strict austerity measures implemented by the Greek Government since the beginning of 2010. Well documented effects of this combination are the increase of the burden of COPD [1], and its pharmacological treatment cost [2], increased death rates from nervous system diseases and mental health problems [3], increased deaths due to adverse events during medical treatment [4], increased rates of suicide attempts particularly in males [5], decrease by nearly 50% of the number of solid organ transplantations from deceased donors [6], poor out-of-hospital outcome of acute coronary syndrome in patients with low annual income [7], decrease of both the duration and the completion of anti-tuberculosis therapy [8], increased infant mortality [9] and dramatic decrease (by 15%) in livebirths rate [10]. In total, the health indicators for the Greek population worsened more than those of other countries similarly affected by recession [11].…”
Section: Introductionmentioning
confidence: 99%